Word Order in Epigraphic Gǝ’ǝz - Bulakh, Maria (Aethiopica, 2012)
The paper offers the results of analysis of word order throughout the epigraphic corpus of Gǝʿǝz. This evidence is mostly in agreement with the data from Classical Gǝʿǝz and confirms that early Gǝʿǝz represents the classical Semitic type of a right-branching language: objects and prepositional phrases mostly follow the verbs, and relative clauses and genitive complements usually follow the head nouns. At the same time, some differences between the syntax of Classical Gǝʿǝz and Epigraphic Gǝʿǝz have been registered, notably in the behaviour of numerals.